A set retarding cement slurry system and its preparation method and application
Patent Information
- Application Number
- CN202310795333.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-06-30
AI Technical Summary
[0006]上述现有技术,在防套变方面取得了成果,但在复杂的套变工况下仍不具备普适性
Smart Images

Figure BDA0004314844640000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of shale gas cementing technology, specifically to a casing deformation mitigation cement slurry system, its preparation method, and its application. Background Technology
[0002] Currently, the common methods to address the issue of casing deformation in shale gas well cementing are to increase the thickness of the cement sheath or the casing wall thickness, and to reduce the elastic modulus of the cement stone, in order to alleviate the casing deformation phenomenon. There is no cementing slurry system specifically designed for preventing casing deformation in shale gas wells.
[0003] CN202210052442.5 discloses a high-density anti-channeling toughness cement slurry system for shale gas cementing, its preparation method, and its application. The system includes G-grade cement, water, composite weighting agent, nano anti-channeling agent, toughening agent, fluid loss reducing agent, retarder, dispersant, and defoamer. The addition of the nano anti-channeling agent not only has no negative impact on the construction performance of the cement slurry, but also promotes the formation of early strength of cement, reduces cement stone permeability, and makes the structure of cement stone more uniform and dense, effectively enhancing the anti-channeling properties of cement stone.
[0004] CN201910113067.9 discloses a cementing slurry system suitable for large-scale segmented fracturing of shale gas horizontal wells, mainly comprising 100 parts oil well cement, 43-46 parts fresh water, 2-4 parts elasticity agent, 1-2 parts anti-channeling agent, 1-3 parts fluid loss reducing agent, 0.4-0.6 parts dispersant, 1-1.5 parts expansion agent, 0.5-2.0 parts retarder, and 0.1-0.5 parts defoamer. The elasticity agent is rubber fiber with a specific surface area ≥7m² / g and a volume compressibility ≥5%, or a mixture of rubber fiber and rubber particles. The cement slurry system of this technology has excellent thickening and anti-channeling properties, as well as comprehensive properties such as elasticity and toughness. It can effectively achieve synchronous deformation of the cement sheath and casing under the alternating load of segmented fracturing, ensuring the long-term integrity of the wellbore seal during the later stages of reservoir stimulation and gas testing operations in shale gas horizontal wells. It effectively prevents the occurrence of casing annular pressure and provides an effective guarantee for long-term production and large-scale fracturing of shale gas horizontal wells.
[0005] CN201410471036.8 discloses a toughening and anti-channeling agent for cement and toughening cement for cementing shale gas horizontal wells. This technology relates to a cement slurry used in cementing shale gas horizontal wells and the toughening additives added thereto. The toughening and anti-channeling agent for cement is composed of styrene-butadiene rubber powder and redispersible latex powder mixed in a 2:1 mass ratio. The styrene-butadiene rubber powder undergoes the following treatment before use: a 1.5% (by mass) silane coupling agent solution is prepared, the styrene-butadiene rubber powder is added, the mixture is allowed to stand for 24 hours, filtered, and dried to form a cement slurry. The resulting system exhibits stable performance, easily adjustable thickening time, water loss of less than 30 ml, a free liquid at a 45-degree angle, and a density difference of 0.50°C. The compressive strength at 24 hours is greater than 30 MPa, the applicable temperature range is 50-120°C, and the thickening time is 110-240 min. The toughening cement for cementing shale gas horizontal wells incorporates the aforementioned toughening and anti-channeling agent. The cement slurry system it produces has good stability and low water loss and separation, which can meet the requirements of multi-stage fracturing of shale gas horizontal wells for cement slurry systems.
[0006] While the aforementioned existing technologies have achieved results in preventing casing deformation, they still lack universal applicability under complex casing deformation conditions. Therefore, there is an urgent need to conduct research on cementing slurries for mitigating casing deformation in shale gas wells, improve cementing quality, ensure casing safety during service, and guarantee efficient shale gas development. Summary of the Invention
[0007] To solve the above-mentioned technical problems, the present invention provides a cement slurry system for mitigating structural changes and its preparation method, wherein the cement slurry system has low production costs and is easy to obtain.
[0008] To achieve the above objectives, the present invention provides a cement slurry system for mitigating deformation, wherein the raw materials of the cement slurry system for mitigating deformation include, by weight percentage: 100 parts of G-grade oil well cement, 3-6 parts of microsilica, 15-50 parts of glass microspheres, 3-6 parts of reinforcing material, 3-5 parts of toughening material, 0-2 parts of stabilizer, 0-2.5 parts of dispersant, 3-6 parts of fluid loss reducer, 0-2.5 parts of retarder, 0.2-0.5 parts of defoamer, 0.2-0.5 parts of defoaming agent, and 70-95 parts of water;
[0009] The toughening material is composed of fibers and carbon materials in a mass ratio of 2-4:1. The fibers include one or more of basalt fibers, alumina fibers, and silicon carbide fibers, and the carbon materials include carbon nanotubes and / or expanded graphite.
[0010] The compressive strength of the glass microspheres is 3000-5000 psi.
[0011] In the above-mentioned cement grout system for mitigating deformation, preferably, the compressive strength of the glass microspheres is 4000 psi.
[0012] This invention reduces the elastic modulus of cement stone without affecting its compressive strength by adding glass microspheres with low compressive strength and toughening materials composed of fiber and carbon materials. Before the cement stone reaches its compressive strength limit and fails, the internal glass microspheres are broken, providing a certain buffer space for the deformation of the casing and gradually enhancing the ability of the cement stone to alleviate casing deformation.
[0013] In the above-mentioned basalt fiber slurry system for mitigating structural changes, preferably, the fiber length of the basalt fiber is 1.5-10 μm.
[0014] In the above-mentioned cement slurry system for mitigating deformation, preferably, the alumina fiber has a fiber length of 3-6 μm.
[0015] In the above-mentioned cement slurry system for mitigating structural changes, preferably, the silicon carbide fiber has a fiber length of 10-15 μm.
[0016] In the above-mentioned cement slurry system for mitigating deformation, preferably, the length of the carbon nanotubes is 10-30 μm.
[0017] In the above-mentioned cement slurry system for mitigating deformation, preferably, the expanded graphite has a particle size of 40-50 μm.
[0018] In the above-mentioned cement slurry system for mitigating structural changes, preferably, the average particle size of the microsilica is 4-10 μm, and the residue on a 45 μm sieve is ≤5%.
[0019] In the aforementioned cement grout system for mitigating structural changes, preferably, the true density of the glass microspheres is 0.38-0.42 g / cm³. 3 More preferably 0.40 g / cm³ 3 The present invention optimizes the true density of glass microspheres. If the true density of glass microspheres is too high, the space they can provide after breakage will be limited.
[0020] In the above-mentioned cement slurry system for mitigating deformation, preferably, the stabilizer is an ore powder stabilizer and / or a polymer stabilizer, more preferably an ore powder stabilizer.
[0021] In the above-mentioned cement slurry system for mitigating deformation, preferably, the dispersant is a condensation polymer of formaldehyde and acetone and / or a polystyrene sulfonate dispersant.
[0022] In the above-mentioned cement slurry system for mitigating water loss, preferably, the water loss reducing agent is a polyacrylamide-based water loss reducing agent.
[0023] In the above-mentioned modified cement slurry system, preferably, the retarder is an acrylamide retarder.
[0024] In the aforementioned defoaming cement slurry system, preferably, the defoamer includes one or more of the following: tributyl phosphate, polyoxypropylene glycerol, and polydimethylsiloxane.
[0025] According to a specific embodiment of the present invention, preferably, the 7-day compressive strength of the cement stone formed by the modified cement slurry system is >20MPa and the elastic modulus is <5GPa.
[0026] According to a specific embodiment of the present invention, preferably, the density of the modified cement grout system is 1.30-1.60 g / cm³. 3 The applicable temperature range is 30-150℃.
[0027] The present invention also provides a method for preparing the above-mentioned deformation mitigation cement slurry system, the method comprising: weighing raw materials in proportion and mixing them, stirring evenly at a speed of 11500-12500 r / min to obtain the deformation mitigation cement slurry system.
[0028] According to a specific embodiment of the present invention, preferably, the preparation method of the sleeve deformation mitigation cement slurry system includes the following steps:
[0029] Weigh out the oil well cement, microsilica, glass microspheres, reinforcing materials, toughening materials, stabilizers, and dispersants in proportion, and mix them evenly to obtain a dry-mixed material;
[0030] Weigh out the water loss reducer, retarder, and defoamer in proportion and stir them evenly in water to obtain a wet-mixed solution.
[0031] At a speed of 3800-4200 r / min, the dry mixture is evenly poured into the wet mixture. After the dry mixture is completely added to the wet mixture, the speed of the agitator is adjusted to 11500-12500 r / min and stirring is continued to obtain the aforementioned deformation mitigation cement slurry system.
[0032] The present invention also provides an application of the above-mentioned casing deformation mitigation cement slurry system in shale gas well cementing and in preventing and / or mitigating casing deformation.
[0033] The technical solution provided by this invention has the following beneficial effects:
[0034] The casing deformation mitigation cement slurry system provided by this invention meets the requirements of cementing operations. Simultaneously, the cement stone has a low elastic modulus, and when formation slippage is significant, it can actively break up to create space, providing room for casing deformation, thus effectively preventing and mitigating casing deformation. In some specific embodiments, the cement stone formed by the casing deformation mitigation cement slurry system of this invention has a 7-day compressive strength > 20 MPa and an elastic modulus < 5 GPa. Detailed Implementation
[0035] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.
[0036] Description of raw materials used in the embodiments of this invention:
[0037] Grade G oil well cement is a high sulfate-resistant (HSR) Grade G oil well cement produced by Dalian Cement Group Co., Ltd.
[0038] The stabilizer is a mature product manufactured by China Petroleum Engineering Technology Research Institute Co., Ltd., and its trade name is "Reinforcing Material for Cementing Oil Wells - Ore Powder DRB-1S".
[0039] Basalt fiber is commercially available, with a fiber length of 1.5-10μm;
[0040] Alumina fibers are commercially available, with a fiber length of 3-6μm;
[0041] The length of silicon carbide fibers is 10-15 μm;
[0042] Carbon nanotubes, 95% purity, with a length of 10-30 μm;
[0043] Expanded graphite is commercially available, with a purity of over 95% and a particle size of 48μm (300 mesh).
[0044] Microsilica is commercially available, with an average particle size of 5μm and a sieve residue of ≤5% on a 45μm sieve.
[0045] The dispersant is a condensation polymer of formaldehyde and acetone or a polystyrene sulfonate dispersant;
[0046] The water loss reducing agent is a type of polyacrylamide.
[0047] The defoamer is one of the commonly used defoamers in this field, such as tributyl phosphate, polyoxypropylene glycerol, and polydimethylsiloxane.
[0048] Example 1
[0049] This embodiment provides a variable-response cement slurry system, the preparation method of which is as follows:
[0050] I. Formula
[0051] The cement slurry formulation, by weight percentage, is as follows: 100 parts Grade G oil well cement, 5 parts microsilica, 10 parts reinforcing material, 4 parts toughening material, 13 parts glass microspheres, 1 part stabilizer, 1.5 parts dispersant, 3.5 parts water loss reducer, 0.8 parts retarder, 0.5 parts defoamer, 0.5 parts antifoaming agent, and 70 parts water; wherein the toughening material is composed of 2 parts basalt fiber and 1 part expanded graphite, uniformly mixed; the true density of the glass microspheres is 0.40 g / cm³. 3 Its compressive strength is 4000 psi.
[0052] II. Preparation Method
[0053] Oil well cement, microsilica, glass microspheres, reinforcing materials, toughening materials, stabilizers, and dispersants were weighed out according to the specified proportions and uniformly mixed to obtain a dry-mix material. A water-loss reducer, retarder, and defoamer were weighed out according to the specified proportions and stirred evenly in water to obtain a wet-mix solution. The dry-mix material was evenly poured into the wet-mix solution at a speed of 4000 rpm. After the dry-mix material was completely added to the wet-mix solution, the mixing cup lid was closed, the mixer speed was adjusted to 12000 rpm, and stirring was continued for 35 seconds to obtain the deformation-reducing cement slurry system. The density of this cement slurry was tested to be 1.6 g / cm³. 3 .
[0054] Example 2
[0055] This embodiment provides a variable-response cement slurry system, the preparation method of which is as follows:
[0056] I. Formula
[0057] The cement slurry formulation, by weight percentage, is as follows: 100 parts Grade G oil well cement, 5 parts microsilica, 10 parts reinforcing material, 4 parts toughening material, 32 parts glass microspheres, 1 part stabilizer, 1.5 parts dispersant, 3.5 parts water loss reducer, 0.8 parts retarder, 0.5 parts defoamer, 0.5 parts antifoaming agent, and 75 parts water; wherein the toughening material is composed of 3 parts silicon carbide fiber and 1 part expanded graphite uniformly mixed; the true density of the glass microspheres is 0.40 g / cm³. 3 Its compressive strength is 4000 psi.
[0058] II. The preparation method is the same as in Example 1. The density of this cement slurry is 1.45 g / cm³. 3 .
[0059] Example 3
[0060] This embodiment provides a variable-response cement slurry system, the preparation method of which is as follows:
[0061] I. Formula
[0062] The cement slurry formulation, by weight percentage, is as follows: 100 parts Grade G oil well cement, 5 parts microsilica, 10 parts reinforcing material, 4 parts toughening material, 50 parts glass microspheres, 1 part stabilizer, 1.5 parts dispersant, 3.5 parts water loss reducer, 0.8 parts retarder, 0.5 parts defoamer, 0.5 parts antifoaming agent, and 78 parts water; wherein the toughening material is composed of 4 parts alumina fiber and 1 part carbon nanotubes uniformly stirred; the true density of the glass microspheres is 0.40 g / cm³. 3 Its compressive strength is 4000 psi.
[0063] II. The preparation method is the same as in Example 1. The density of this cement slurry is 1.3 g / cm³. 3 .
[0064] Comparative Example 1
[0065] This comparative example provides a cement slurry system with the same formulation and preparation method as Example 1, except that no toughening material is added in this comparative example, and the true density of the glass microspheres used is 0.63 g / cm³. 3 The compressive strength is 15,000 psi; at the same time, in order to keep the density of the cement paste unchanged, the weight of water is changed to 68 parts.
[0066] Comparative Example 2
[0067] This comparative example provides a cement slurry system with the same formulation and preparation method as Example 2, except that no toughening material is added in this comparative example, and the true density of the glass microspheres is 0.60 g / cm³. 3 The compressive strength is 12000psi; at the same time, in order to keep the density of the cement paste unchanged, the weight of water is changed to 73 parts.
[0068] Comparative Example 3
[0069] This comparative example provides a cement slurry system with the same formulation and preparation method as Example 3, except that no toughening material is added in this comparative example, and the true density of the glass microspheres is 0.60 g / cm³. 3 The compressive strength is 12000psi; at the same time, in order to keep the density of the cement paste unchanged, the weight of water is changed to 76 parts.
[0070] Experimental Example
[0071] Experiments were conducted in accordance with the national standard GB / T 19139-2012 "Test Methods for Cement in Oil Wells" to evaluate the conventional engineering properties (density, fluidity, API water loss), compressive strength, and modulus of elasticity of the cement slurry system.
[0072] The main experimental instruments include: 30-60 type corrugated agitator; TG7370D type pressure curing kettle, Shenyang Taige Petroleum Instrument Equipment Manufacturing Co., Ltd.; HH-420 type constant temperature digital display water tank, Changzhou Yineng Experimental Instrument Factory; YAW-300B hydraulic pressure testing machine, Jinan Xinshijin Testing Machine Co., Ltd.
[0073] This experimental example also uses the following method to test the breakage rate of glass microspheres under specified conditions:
[0074] 1. Measurement Principle
[0075] The breakage rate is determined by the change in density of the sample before and after compression under a specified pressure.
[0076] 2. Instruments and equipment
[0077] Strength tester, nitrogen (99.9% purity), analytical balance.
[0078] 3. Experimental Procedure
[0079] (1) First, take (2-5)g of sample for true density measurement. The instrument used is the 3H-2000TD2 true density measuring instrument produced by Best Instrument Technology (Beijing) Co., Ltd. (or other instruments with the same true density measurement function can be selected for measurement).
[0080] (2) Take 2-5 g of the same batch and put it into the sample chamber. Place the sample chamber into the high-pressure chamber and tighten the bolts of the high-pressure chamber.
[0081] (3) Open the nitrogen valve, fill with nitrogen, and maintain the nitrogen pressure at the required pressure for 5 minutes. After releasing the pressure, take out the sample and measure the true density. The instrument used is the 3H-2000TD2 true density measuring instrument produced by Best Instrument Technology (Beijing) Co., Ltd. (or other instruments with the same true density measurement function).
[0082] 4. Breakage rate calculation
[0083] The density of the samples before and after compression is calculated using the following formula:
[0084] R=ρ0×(ρ2-ρ2) / ρ2 / (ρ0-ρ1)×100
[0085] In the formula:
[0086] R—Breakage rate under specified conditions, %;
[0087] ρ0—True density of the sample when completely broken, g / cm³ 3 ;
[0088] ρ1—Pre-compression density of the sample, g / cm³ 3 ;
[0089] ρ2 — density of the sample after compression, g / cm³ 3 .
[0090] The test results of the cement slurry systems of the above embodiments and comparative examples are shown in Table 1.
[0091] Table 1 Performance test results of cement slurry system
[0092]
[0093] As shown in Table 1, the flowability of the cement slurry systems in Examples 1-3 is greater than 20 cm and the API water loss is less than 50 mL, which meets the requirements for cementing construction. The cement stone formed by the cement slurry systems in Examples 1-3 has a 7-day compressive strength greater than 20 MPa and an elastic modulus less than 5 GPa, which shows good performance and meets the requirements for cementing sealing.
[0094] The test results of Comparative Examples 1-3 show that without the addition of toughening materials, the cement stone formed has a compressive strength greater than 20 MPa, but a high 7-day elastic modulus. The cement stone has poor deformation ability during stratum slippage, which easily leads to stress concentration. In addition, when the stratum stress reaches the limit of the cement stone's compressive strength, the cement stone cracks. At this time, the internal high-compression glass microsphere structure is basically intact and cannot provide space for sleeve deformation.
[0095] Comparing the results of Comparative Example 1 and Example 1, it can be seen that the conventional properties of the cement slurry, such as API water loss, fluidity, and compressive strength, are not significantly different and both meet the construction requirements. Compared with Comparative Example 1, after adding toughening materials and replacing the glass microspheres with a compressive strength of 4000 Pasi in Example 1, the elastic modulus of the cement stone decreased from 7.94 GPa to 4.92 GPa. The brittleness of the cement stone decreased significantly. Before the cement stone reached its compressive strength limit and failed, the internal glass microspheres had already broken (breakage rate of 95.1%), providing a larger deformation space and a certain buffer space for the deformation of the casing.
[0096] Compared with Comparative Example 2, after adding toughening materials and replacing the glass microspheres with a compressive strength of 4000 Pasi in Example 2, the conventional properties of cement slurry such as API water loss, fluidity, and compressive strength did not change much and both met the construction requirements. However, the elastic modulus of Example 2 decreased by 2.95 GPa, and the elastic modulus of cement stone was significantly reduced. When slippage occurs in the stratum, the breakage of glass microspheres (breakage rate of 96.6%) can provide a large deformation space, thereby providing a certain buffer space for casing deformation.
[0097] Compared with Comparative Example 3, after adding toughening materials and replacing the glass microspheres with a compressive strength of 4000 Pasi in Example 3, the conventional properties of cement slurry such as API water loss, fluidity, and compressive strength did not change much and both met the construction requirements. However, the elastic modulus of Example 2 decreased by 2.91 GPa, and the elastic modulus of cement stone was significantly reduced. When slippage occurs in the stratum, the breakage of glass microspheres (breakage rate of 95.1%) can provide a large deformation space, thereby providing a certain buffer space for casing deformation.
[0098] In summary, the cement grout system for mitigating deformation provided by this invention has a density of 1.30-1.60 g / cm³. 3 It is applicable to temperatures ranging from 30 to 150℃, with a 7-day cement stone compressive strength greater than 20MPa and an elastic modulus less than 5GPa. It also exhibits good settlement stability and rheological properties, meeting the requirements for cementing construction.
[0099] The embodiments described above are merely illustrative of implementation methods of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications, equivalent substitutions, and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this patent should be determined by the appended claims.
Claims
1. A cement grout system for mitigating structural changes, comprising, by weight, the following raw materials: 100 parts of Grade G oil well cement, 3-6 parts of microsilica, 15-50 parts of glass microspheres, 3-6 parts of reinforcing material, 3-5 parts of toughening material, 0-2 parts of stabilizer, 0-2.5 parts of dispersant, 3-6 parts of fluid loss reducer, 0-2.5 parts of retarder, 0.2-0.5 parts of defoamer, 0.2-0.5 parts of defoaming agent, and 70-95 parts of water; The toughening material is composed of fibers and carbon materials in a mass ratio of 2-4:
1. The fibers include one or more of basalt fibers, alumina fibers, and silicon carbide fibers. The carbon materials include carbon nanotubes and / or expanded graphite. The basalt fibers have a fiber length of 1.5-10 μm; the alumina fibers have a fiber length of 3-6 μm; and the silicon carbide fibers have a fiber length of 10-15 μm. The glass microspheres have a compressive strength of 3000-5000 psi and a true density of 0.38-0.42 g / cm³. 3 ; The cement paste formed by the aforementioned modified cement grout system has a 7-day compressive strength > 20 MPa, an elastic modulus < 5 GPa, and a density of 1.30-1.60 g / cm³. 3 The applicable temperature range is 30-150℃.
2. The cement grout system for mitigating deformation according to claim 1, wherein, The length of the carbon nanotubes is 10-30 μm.
3. The cement grout system for mitigating deformation according to claim 1, wherein, The expanded graphite has a particle size of 40-50 μm.
4. The cement grout system for mitigating deformation according to claim 1, wherein, The true density of the glass microspheres is 0.40 g / cm³. 3 .
5. The cement grouting system for mitigating deformation according to claim 1, wherein, The average particle size of the microsilicon is 4-10 μm, and the residue on a 45 μm sieve is ≤5%.
6. The cement grout system for mitigating deformation according to claim 1, wherein, The stabilizer is an ore powder stabilizer and / or a polymer stabilizer.
7. The cement grouting system for mitigating deformation according to claim 1, wherein, The dispersant is a condensation polymer of formaldehyde and acetone and / or a polystyrene sulfonate dispersant.
8. The cement grouting system for mitigating deformation according to claim 1, wherein, The water loss reducing agent is a polyacrylamide-based water loss reducing agent.
9. The cement grouting system for mitigating deformation according to claim 1 or 8, wherein, The retarder is an acrylamide-based retarder.
10. The cement grouting system for mitigating deformation according to claim 1 or 8, wherein, The defoamer includes one or more of the following: tributyl phosphate, polyoxypropylene glycerol, and polydimethylsiloxane.
11. A method for preparing the cement grout system for mitigating deformation according to any one of claims 1-10, comprising: Weigh out the oil well cement, microsilica, glass microspheres, reinforcing materials, toughening materials, stabilizers, and dispersants in proportion, and mix them evenly to obtain a dry-mixed material; Weigh out the water loss reducer, retarder, defoamer, and foam suppressant in proportion and stir them evenly in water to obtain a wet-mixed solution; At a speed of 3800-4200 r / min, the dry mixture is evenly poured into the wet mixture. After the dry mixture is completely added to the wet mixture, the speed of the agitator is adjusted to 11500-12500 r / min and stirring is continued to obtain the aforementioned deformation mitigation cement slurry system.
12. The application of the casing deformation mitigation cement grout system according to any one of claims 1-10 in cementing shale gas wells and preventing and / or mitigating casing deformation.
Citation Information
Patent Citations
Toughening and anti-channeling agent for cement and toughening cement for shale gas horizontal well cementing
CN104291733B
Well cementation cement paste system applicable to large-size staged fracturing of shale gas horizontal well
CN109761547A
A high-density, anti-channeling, tough cement slurry system for shale gas cementing, its preparation method, and its application.
CN114426415B
Expanded flexible well cementing grout and preparation method thereof
CN104371678A